Association of killer cell immunoglobulin-like receptor (KIR) genes and their HLA ligands with susceptibility to Behçet's‎ disease. (4th March 2018) - Mohammad-Ebrahim, H; Kamali-Sarvestani, E; Mahmoudi, M; Beigy, M; Karami, J; Ahmadzadeh, N; Shahram, F
Abstract : Objectives : Behçet's disease (BD) is a systemic inflammatory disorder with remissions and exacerbations. It is thought that defects in the natural killer (NK) cell repertoire may be involved in BD through killer cell immunoglobulin-like receptors (KIRs). This study aimed to evaluate KIR and HLA genes, their interactions in BD patients, and their associations with clinical manifestations. Method : The presence or absence of KIR and HLA alleles and genotypes was analysed by polymerase chain reaction sequence-specific primer on genomic DNA of 397 BD patients and 300 healthy controls. Results : None of the KIR genes showed significant effects on BD susceptibility. HLA-C1 Asn80 showed a protective effect against BD, whereas HLA-C2 Lys80, HLA-B-Bw4 Ile80, HLA-B5, and HLA-B51 were associated with a susceptibility risk for BD. In the combination of KIR and HLA genes, the frequencies of HLA genotypes no. 2, 3, 5, and 8, and inhibitory KIR no. 4 were significantly higher in patients than in controls. The frequencies of KIR genotype no. 3 and HLA genotypes no. 1, 4, 6, 7, and 9 were significantly lower in patients than in controls. There were many associations between KIR and HLA genes with clinical features of BD. Conclusion : Differences in the frequency of HLA genes, KIR–HLA interactions, and genotypes between BD and healthy controls and their associations with clinical manifestations indicate that NK cells are involved in BD pathogenesis. The observed differences indicated an NK cell activity imbalance in BD patients, and suggest a role of the KIR-HLA repertoire in the development of BD.